The Role of Emotions and Emotional Regulation in Driving Behaviors - Bedoui , Aicha; Ghezal , Naima; Moufida , Zekkour Mouhamed (Journal of Ecohumanism, 2025)
Emotions and emotional regulation play a significant role in influencing driving behaviors. Negative emotions such as anger and frustration may negatively affect concentration and attention while driving, thereby increasing the risk to the driver and others. In contrast, positive emotions such as happiness and relaxation can enhance focus and quick responsiveness, contributing to improved driving performance. The ability to manage and control negative emotions using emotional regulation strategies plays a pivotal role in maintaining focus and safe driving performance. Conversely, poor emotional regulation is associated with an increased risk of traffic accidents. Enhancing emotional regulation skills among drivers may contribute to improving driving safety. Overall, the research emphasizes the importance of emotions and the ability to regulate them in influencing driving behaviors and road safety.